Heavy mineral mining in the Atlantic Coastal Plain of Florida and Georgia and the chemical and physical characteristics of the deposits - F. L. Pirkle; W. A. Pirkle; E. C. Pirkle; D. L. Pirkle (Society for Mining, Metallurgy & Exploration, 2005)
Heavy minerals have been mined from the sands of the United States’ Atlantic Coastal Plain since the early part of the twentieth century. Production of ilmenite from beach sands near Mineral City (Ponte Vedra), Florida, began in 1916. The first reported large-scale recovery of zircon in Florida was reported from this deposit in 1922 and of rutile in 1925. These operations ceased in 1929. Today the Ponte Vedra Country Club and Golf Course is situated in the center of the former mining site. In 1942 heavy-mineral operations were established on 202 hectares of land situated in Duval County, Florida. The location is about 16 kilometers east of the center of Jacksonville, Florida, in an area known as Arlington. This operation demonstrated that low-grade sand containing only 2 to 3 percent titanium minerals could be concentrated economically with the Humphreys spiral and that the oxides could be separated from the heavy silicates by electrostatic methods. Much of this area is now covered by a large mall and is a major retail- commercial center. Between 1958 and 1964 the Skinner tract, a deposit about 4 kilometers south of the above deposit, was mined. Today the area of this deposit is known as Deerwood, a gated country club community on the southside of Jacksonville. Further inland, E.I. du Pont de Nemours and Co. has been mining heavy minerals from a physiographic feature known as Trail Ridge since 1948, and a deposit near Green Cove Springs, Florida has been in production since 1972. Since the start of heavy-mineral mining in the southeastern United States, nine heavy-mineral ore bodies either have been or are being exploited in Florida and Georgia. Other deposits either have been lost to mining or are yet to be mined. These deposits have different origins. Some formed along shorelines at the heights of marine transgressions while others formed on regressional beach ridge plains during periods of temporary stillstands or slight transgressions. These different origins are reflected in the chemical and physical characteristics of the deposits. Ilmenite in older, more western deposits has a higher TiO2 content than ilmenite in younger, more eastern deposits. TiO2 content does not very with north-south direction. Garnet and epidote are absent or rare in the older Trail Ridge deposits, but progressively become common in the younger Duval Upland, Crestal Pamlico, and Holocene deposits. Grain size is coarsest for Trail Ridge sediments and finest for sediments in Duval Upland and Crestal Pamlico deposits. The average grain size for Holocene deposits is intermediate between Trail Ridge and Duval Upland deposits. The two models for the origin of the heavy-mineral deposits – deposits formed at the height of major marine transgression; and deposits formed during periods of temporary stillstands or slight transgressions that occur during a general marine regression; - are consistent with known sedimentological data and depositional trends.